Organic Waste Composting: A Resource Recovery Approach towards Sustainable Environment (Proceedings of the World Conference on Waste Management, 2019)
Organic waste (including kitchen, garden/lawn, and agricultural waste) were subjectto composting through static pile and soil pit composting techniques to determine the bestmethod for managing the organic fraction of Municipal Solid Waste (MSW). Theseconventional methods were used with some innovations (by using soil as seed compost andaeration assembly) to increase the efficiency while keeping the process cost effective.Quantitative parameter analysis of initial feedstocks such as weight, moisture content (MC)and bulk density (BD) were measured before setting up each experiment. Temperaturevariation was monitored on a daily basis and measurement of CO2 emission on weekly basis.Moreover, mixing of feedstock for aeration and applying water for optimum moisture contentwere also subject to weekly activities. Final compost from each experiment was analyzedagainst physical and chemical parameters such as colour, MC, BD, water holding capacity, pHand electrical conductivity. Aerobic soil pit showed better results among other compostingtechniques with with BD of 530±0.01 kg/m3, MC 37.40±0.26 %, water holding capacity94±0.45 %, pH 8.00±0.10 and electrical conductivity 1.06±14.42 dS/m. Based on theexperiment’s results, there were two conclusions drawn, first the application of soil proved tobe very helpful as seed compost in a static pile showing good results. Secondly, soil pitcomposting with modification of passive aeration also proved it as a potential technique tomanage organic waste.
Keywords: Composting; Resource Recovery; Waste Management; Sustainability